480. Reduction in Clostridium difficile Infection Rates Following a Prevention Collaborative in Orange County, California, 2014–2017. (26th November 2018) - Rizzo, Kyle; Garcia, Erin; Zahn, Matthew; Yi, Sarah H; Epson, Erin
Abstract: Background: The California Department of Public Health (CDPH) Healthcare-Associated Infections (HAI) Program and Orange County Health Care Agency convened a Clostridium difficile infection (CDI) prevention collaborative with health care facilities in Orange County (OC) to reduce CDI incidence in the region. Methods: We invited all 34 hospitals and 76 skilled nursing facilities (SNF) in OC to participate from June 2015 to June 2016. Participants received onsite infection control and antimicrobial stewardship assessments, trainings, and an interfacility transfer communication improvement initiative. We used an interrupted time-series design and segmented regression analysis to evaluate monthly hospital-onset (HO) and community-onset (CO) CDI rates for acute care hospitals (ACH) reporting HAI data to CDPH via the National Healthcare Safety Network. The baseline period included 17 months (January 2014–June 2015) and the collaborative period 28 months (September 2015–December 2017). All OC acute care hospitals were included in the CO-CDI model to account for direct and indirect effects of the collaborative. We included only participating ACH in the HO-CDI model. For informal comparisons, we assessed changes in CO-CDI for ACH in three San Francisco Bay Area counties and HO-CDI rates in nonparticipant OC acute care hospitals. Results: Collaborative participants comprised 15 ACH, three long-term acute care hospitals, one children's hospital, and 20 SNF; all but two SNF received an onsite assessment. Unadjusted, baseline pooled mean HO-CDI rates were 8.5 cases per 10, 000 patient days for participant ACH, and CO-CDI rates were 4.9 cases per 1, 000 admissions in OC acute care hospitals. During the collaborative period, HO-CDI rates in OC participant ACH decreased 2% per month (incidence rate ratio [IRR]: 0.98, 95% CI: 0.96, 0.99; P < 0.001). HO-CDI rates among OC nonparticipant ACH ( N = 10) did not change during the same timeframe (IRR: 0.99, 0.96, 1.02; P = 0.37). During the collaborative period, Orange County CO-CDI rates also declined 2% per month (IRR: 0.98, 0.97, 0.99; P < 0.001); no changes in CO-CDI were observed among ACH ( N = 27) in the comparison counties (IRR: 1.00, 0.99, 1.01; P = 0.78). Conclusion: Our analysis of acute care hospitals in Orange County provides evidence that coordinated, regional multifacility initiatives can reduce CDI incidence. Disclosures: All authors: No reported disclosures.